Harvest control rules of pelagic fisheries in the Bali Strait, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harlyan LI, Badriyah L, Rahman MA, Sutjipto DO, Sari WK. 2021. Harvest control rules of pelagic fisheries in the Bali Strait, Indonesia. Biodiversitas 23: 947-953. Multispecies pelagic fisheries have contributed as the main fishery production for the Bali Strait fisheries. To maintain the sustainability of the fish stock, sets of harvest control rules (HCRs) have been introduced in terms of fishery management. Conventional single-species surplus production models have been used extensively to determine the future annual allowable biological catch (ABC). However, they may not technically apply to multispecies fishery management. The feedback harvest control rule HCR has been validated and applied to maintain the catch variability of the multispecies fishery. This study aims to technically compare the use of the surplus production model and the feedback HCR in the ABC estimation. The catch and effort data series of the three dominant species from 2010-2019, collected from Pengambengan and Muncar fishing port, were analyzed by two HCRs, the Schaefer surplus production model and the feedback HCR to obtain the ABC. As a result, the Schaefer model showed a higher estimation of ABC than the feedback HCR because the feedback HCR may reflect the recent historical catch consistent with precautionary principles. The feedback HCR showed an initial step toward sustainably managing multispecies fisheries while dealing with unavailability in species-specific data conditions.
Keywords: Allowable biological catch, feedback HCR, mixed-species data, multispecies fishery, Schaefer model